2002
DOI: 10.1046/j.1365-2885.2002.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal insufficiency on the pharmacokinetics and pharmacodynamics of benazepril in cats

Abstract: The effect of renal insufficiency was studied on the pharmacokinetics (PK) and pharmacodynamics (PD) of the angiotensin-converting enzyme (ACE) inhibitor benazepril in cats. The active metabolite of benazepril, benazeprilat, is eliminated principally ( approximately 85%) via biliary excretion in cats. A total of 20 control animals and 32 cats with moderate renal insufficiency induced by partial nephrectomy were used. Assessments were made at steady state after treatment with placebo or benazepril (0.25-2 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…Relative or absolute hyperaldosteronism could be a possible cause. Hypertensive cats with naturally occurring CKD and experimentally induced renal insufficiency respond poorly to treatment with angiotensin‐converting enzyme inhibitors (ACEi) 4, 6, 7, 8. The study by Steele and colleagues evaluated the effect of ACEi (benazepril or enalapril) therapy in cats with systemic hypertension and CKD.…”
mentioning
confidence: 99%
“…Relative or absolute hyperaldosteronism could be a possible cause. Hypertensive cats with naturally occurring CKD and experimentally induced renal insufficiency respond poorly to treatment with angiotensin‐converting enzyme inhibitors (ACEi) 4, 6, 7, 8. The study by Steele and colleagues evaluated the effect of ACEi (benazepril or enalapril) therapy in cats with systemic hypertension and CKD.…”
mentioning
confidence: 99%
“…Because ACE inhibitors carry the risk of hypotension and acute reduction in glomerular filtration [23], we chose to increase the dose of BH gradually to the final dose of 1 mg/kg/day, the dose found sufficient to inhibit ACE activity in cats [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Of the available ACE inhibitors, BH is different in that it is excreted in urine and bile [45]. Pharmacokinetic studies showed that in cats, up to 85% of benazeprilat, the active metabolite of BH, is eliminated via biliary excretion [18], and repeated oral administrations of BH result in a little accumulation of benazeprilat [17]. Similarly, clearance of plasma benazeprilat was found to increase in dogs with experimentally induced renal insufficiency, while that of enalapril, another ACE inhibitor, was decreased to 40 to 55% [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cats, benazeprilat is excreted predominantly (about 85%) by the liver. Similarly, renal dysfunction does not alter benazeprilat pharmacokinetics in this species [9]. One finding from these studies is that, due to the highly complicated pharmacology of ACE inhibitors, it is impossible to predict the effect of renal dysfunction on the disposition of ACE inhibitors only from studies in healthy animals.…”
Section: Pharmacokinetics and Pharmacody-namic/pharmacokinetic Relatimentioning
confidence: 96%